2021
DOI: 10.13189/ujaf.2021.090318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Goods and Services Tax on Indirect Tax Revenue of India: With Special Reference to Odisha State

Abstract: Goods and Services Tax is considered to be one of the revolutionary tax reforms in India since independence. The foundation of this new taxation system is to remove the cascading effect and increase the tax revenue with more transparent mechanism. The present paper is an attempt to assess the impact of this new taxation system on indirect tax revenue of India in general and of Odisha in specific. The study is analytical in nature and is based on published data. Collection of revenue under goods and services ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Mukherjee (2020) found in their study that the adoption of the GST in India has reduced the GST capacity of the Indian states. Similarly, Dey (2021) also found that the Indian states are unable to generate sufficient revenue under the GST regime and will face difficulties in revenue generation in case of the termination of GST compensation to states by the central government in the near future. Nayaka and Panduranga (2020) also revealed that although the registrations, filing of GST returns and tax collections of the Karnataka state are increasing rapidly after the GST adoption, but the release of the compensation cess by the central government is constantly delayed.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Mukherjee (2020) found in their study that the adoption of the GST in India has reduced the GST capacity of the Indian states. Similarly, Dey (2021) also found that the Indian states are unable to generate sufficient revenue under the GST regime and will face difficulties in revenue generation in case of the termination of GST compensation to states by the central government in the near future. Nayaka and Panduranga (2020) also revealed that although the registrations, filing of GST returns and tax collections of the Karnataka state are increasing rapidly after the GST adoption, but the release of the compensation cess by the central government is constantly delayed.…”
Section: Resultsmentioning
confidence: 97%
“…The comparative result affirms (refer Table 1) that after the adoption of GST in India, the efficiency ratio of the Indian states has reduced drastically. Dey (2021) found that Indian states are unable to generate sufficient revenue as per the expectations under the GST regime and will face difficulties in case of the abolishment of GST compensation to states by the central government in near future.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Permadi & Wijaya (2022) in their research revealed that the service sector is a sector with high productivity, which can be seen from its relatively largest contribution compared to other sectors in Gross Domestic Revenue (GDP). More specifically, a study provides results that the imposition of taxes on the consumption of goods and services makes a significant contribution to increasing tax revenue, especially indirect taxes (Dey, 2021).…”
Section: Introductionmentioning
confidence: 99%